THE ANALYSIS OF THE EFFECTS OF CAPITAL ADEQUACY RATIO, OPERATIONAL COST COMPARING TO THE OPERATIONAL REVENUE, NET INTEREST MARGIN, NON-PERFORMING LOAN AND LOAN TO DEPOSIT RATIO UPON THE RETURN ON EQUITY (Empirical Study of Company Banking registered in the List of BEI for the period of 2012-2015) - Gilang Ramadhan Fajri (The Accounting Journal of Binaniaga, 2018)
This research is an empiric study to do a research on the Analysis of the Effects of Capital Adequacy Ratio, Operational Cost comparing to the Operational Revenue, Net interest margin, Non-Performing Loan and Loan to Deposit Ratio upon the Return on Equity (Empirical Study on the Company Banking listed on BEI for the period of 2012-2015), sampling technique has applied the purposive sampling in order to get the samples of 30 companies. The aims of this research are to prove that the effects of Capital Adequacy Ratio (CAR), Operational costs comparing to the Operational Revenue (BOPO), Net interest Margin (NIM), Non-Performing Loan (NPL) netto and Loan to Deposti Ratio (LDR) upon the performance of bank which is measured by Return on Equity (ROE) and which variables that have been the most dominant affecting Return on Equity (ROE). The Analytical technics has applied multiple linear regression and hypothesis test has used t-statistics to examine partial regression coefficient and f-statistics to examine the feasibility of the research model using the level of significance of 5 %. Besides that, classical assumption test has been done covering normality test, multicollinearity test, heteroscedasticity test and auto correlation test.Key words:  Capital Adequacy Ratio (CAR), Operational Cost comparing to the Operational Revenue (BOPO), Net Interest Margin (NIM), NonPerforming Loan (NPL). Loan to Deposit Ratio (LDR), Return on Equity (ROE).